PENGARUH PIJAT OKSITOSIN TERHADAP KELANCARANASI (AIR SUSU IBU) PADA IBU NIFAS DI BPM (BIDAN PRAKTEK MANDIRI) BIDAN DIAN ROSNURMILA, S.S.T., MA. Kes TANGERANG SELATAN TAHUN 2020 - Riswahyuni Widhawati; Amelia Ramawati (Jurnal Kesehatan STIKes IMC Bintaro, 2022)
Breast milk is the best food for babies. Components of food substances are available in an ideal an balanced form for optimal digestion and absorption by the baby. One way to increase the production and smoothness of breast milk, one of which is oxytocin massage. This study aims to identify and determine the effect of oxytocin massage on the fluency of postpartum breastfeeding in midwives Dian Rosnurmila, S.S.T., MA.Kes. The sample in this study were 22 respondents who were determined by non probability sampling technique with qouta sampling method. analysis of research data using the Wilcoxon Signed Rank Test. The results of the study used a pre experimental method with one group pre test post test research design showing that the result obtained were as many as respondents who were willing to exist 22 respondents who were willing, consisting of ages 20-25 (45.5%), 26-30 (40.9%), 31-35 (13.6%). From the results of the statistical test, the value of P = 0.000, where this number is <0.05, it can be concluded that H0 is rejected and Ha is accepted so that it can be ascertained that there is a significant influence between the oxytocin massage variable on the smoothness of breastfeeding. Expected to be able to increase the production of breastmilk in breastfeeding mothers can use oxytocin massage therapy which is cheap, practical and natural.